Effect Of Debt Financing On Financial Performance Of Listed Non-Financial Firms In Kenya - Kibunja, Philip Njau; Fatoki, Olanrewaju Isola (Archives of Business Research, 2020)
This study sought to examine the effect of debt financing on the financial performance of non-financial firms listed on the Nairobi Securities Exchange in the five-year period 2013 to 2017. Using a sample of 23 listed non-financial firms data was collected from published financial statements of the sampled firms and analysed statistical using the panel data regression method. The independent variables were short-term, medium term and long-term debt while the explained variable was return on equity. Three control variables, firm size, sales growth and growth opportunities, were included and considered as having an effect on the relationship between the independent and dependent variables. The study results observed that medium-term debt had a negative and statistical significant relationship with return on equity. Long-term debt had a positive but statistically insignificant relationship while short-term debt had a negative relationship with return on equity.